2005
DOI: 10.1007/s11258-004-2846-3
|View full text |Cite
|
Sign up to set email alerts
|

Endozoochorous seed dispersal by cattle and horse in a spatially heterogeneous landscape

Abstract: Seed dispersal has become an important issue in plant ecology and restoration management. In this paper we examined dung germinating seed content and seed deposition patterns of horses (Shetland and Konik breeds) and Scottish Highland cattle grazing two coastal dune nature reserves. Two times 2.5 l of fresh dung from each type of herbivore were collected during seven sessions in the main fruiting season. Dung samples were placed under greenhouse conditions after drying and cooling. Animal defecation patterns w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 30 publications
4
123
1
3
Order By: Relevance
“…In the case of ungulates ranging in temperate grassland systems, however, this as yet remains to be quantified. Although these animals mainly disperse dry, inconspicuous, usually small-sized fruits or seeds (Cosyns et al, 2005;Malo & Suarez, 1995;Pakeman, Digneffe, & Small, 2002), suchlike seeds are known to suffer high post-dispersal predation rates, too (Hulme & Benkman, 2002). For instance wood mice (Apodemus sylvaticus) and harvest mice (Micromys minutus) -both known to occur within the 'Westhoek' reserve (Smeers, 2001) -are known to forage for grass seeds in WesternEuropean grasslands (Edwards & Crawley, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of ungulates ranging in temperate grassland systems, however, this as yet remains to be quantified. Although these animals mainly disperse dry, inconspicuous, usually small-sized fruits or seeds (Cosyns et al, 2005;Malo & Suarez, 1995;Pakeman, Digneffe, & Small, 2002), suchlike seeds are known to suffer high post-dispersal predation rates, too (Hulme & Benkman, 2002). For instance wood mice (Apodemus sylvaticus) and harvest mice (Micromys minutus) -both known to occur within the 'Westhoek' reserve (Smeers, 2001) -are known to forage for grass seeds in WesternEuropean grasslands (Edwards & Crawley, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Dispersules were on average 1.60 mm in length for A. capillaris and 2.78 mm for P. pratensis (n ¼ 20 each, seeds plus glumes). Cosyns, Claerbout, Lamoot, and Hoffmann (2005) found both grasses to be viably present in dung of cattle, horses and ponies in the 'Westhoek' reserve. Period of seed set is August to October for the former, and August for the latter (Grime, Hodgson, & Hunt, 1988).…”
Section: Main Experimentsmentioning
confidence: 93%
“…Many species of this family are frequently reported as dispersed endozoochorically by large ungulates [5,11,30,47]. Based on published data we expected that moose would serve as a good seed vector of the Fabaceae, which are well represented in both study sites.…”
Section: Discussionmentioning
confidence: 86%
“…During the last two decades, endozoochoric seed dispersal has been reported to be mediated in the temperate zone of Europe by domesticated animals, e.g. : cattle [5,6], horse [5,7], sheep [8,9], reindeer [10], and many wild European herbivores: European bison [11], red deer [12,13], fallow deer [13,14], roe deer [13,15], hare [16], rabbit [17,18], and omnivorous wild boar [15]. All these studies have shown the great potential of endozoochoric plant dispersal and the possible role of this process in the recolonization of land after glaciation [19,20], as well as the possible use of animals as seed vectors during the process of habitat restoration [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, if encountered in archaeobotanical research, seeds of J. gerardii can occur in much higher concentrations than established at Fectio, and therefore van Zeist (1974) excluded this species from the 'seed sum'. Cosyns et al (2005) show that especially Juncus seeds are effectively dispersed through endozoochory. Wells and Lauenroth (2007) emphasize that a suitable environment is a prerequisite for the invasion of local plant communities by species from greater distance.…”
Section: Origin Of Salt-tolerant Plant Speciesmentioning
confidence: 96%